2021
DOI: 10.1063/5.0037964
|View full text |Cite
|
Sign up to set email alerts
|

Study of formation mechanism of double metal plasma jets in a low-current pulsed vacuum arc discharge

Abstract: Plasma jet formation was studied in a vacuum arc configured with a conical cathode located inside a hollow cylindrical anode. The outside of this anode was insulated, except at a 0.4 mm diameter micropore. The grounded vacuum chamber also served as an anode. The hollow cylindrical anode was connected to the grounded chamber anode through a resistor R. 170 A 14 μs arcs were excited by a pulse generator comprised of a series connection of a 0.1 F capacitor bank charged to 12 kV, a 200 μH inductor, and a 30 Ω res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Taking into account the discussion above, the electron field emission [18,19] and Hump theory [20], and our previously obtained results [8], a simplified circuit diagram of the charged As shown in Figure 11, it was concluded that the operation mechanism of the AC d -µCAT was as follows [8]. First, when a high voltage was applied on the μCAT, a strong electric field E c formed on its cathode surface.…”
Section: Operation Mechanism Of the Ac D -µCatmentioning
confidence: 74%
See 4 more Smart Citations
“…Taking into account the discussion above, the electron field emission [18,19] and Hump theory [20], and our previously obtained results [8], a simplified circuit diagram of the charged As shown in Figure 11, it was concluded that the operation mechanism of the AC d -µCAT was as follows [8]. First, when a high voltage was applied on the μCAT, a strong electric field E c formed on its cathode surface.…”
Section: Operation Mechanism Of the Ac D -µCatmentioning
confidence: 74%
“…To quantitatively evaluate the directional ejection length of the plasma jet ejected from the insulating sleeve nozzle and produced by the different μCAT structures, light intensity distributions of the discharge images shown in Figure 3 were calculated using the simulation software of MATLAB [8]. As an example, for the AC s -µCAT structure, the calculated result based on Figure 3b is shown in Figure 4, where values of light intensity in the colour bar were dimensionless normalised data.…”
Section: Visual Appearance Of the Discharge Phenomenonmentioning
confidence: 99%
See 3 more Smart Citations